The Funding of Economics Research: Does Social Capital Matter for Success at the National Science Foundation? - Feinberg, Robert M.; Price, Gregory N. (The Review of Economics and Statistics, 2004)
Utilizing data on research proposals submitted to the National Science Foundation (NSF) Economics Program over a 5-year period, this paper examines whether the social capital stock of grant applicants enhances their access to research resources by increasing the probability of being awarded a research grant. We estimate latent-variable specifications of the NSF decision to fund a research proposal. Our results show that, given ability, being a National Bureau of Economic Research associate increases the probability of a research proposal being funded. We interpret this as being consistent with the hypothesized causal effects of social capital.